LGBTI youth shamelessness and safety called "bullying": Beyond Valentine Road. Issue 2 (3rd April 2017) - Jones, Tiffany
ABSTRACT: Lesbian, gay, bisexual, transgender, and intersex (LGBTI) identities are expected first and foremost to be dominated by shame. American student Larry/Leticia King was not ashamed in exercising their United Nations–recognized right to access an education free from discrimination on the basis of sexual orientation, gender identity, and expression. Speaking freely of crushes on boys and exploring increasingly feminine accessories at school, King faced immense hostility in a small-town Oxnard school, and arguments still echoed in conservative media and organizations resistant to LGBTI education rights at many levels to this day. This review considers how the demonization of LGBTI youth shamelessness and safety—used to justify King's murder by school community members in the film Valentine Road —is both an ongoing problem in global LGBTI education rights debates and a danger to LGBTI students and those who advocate for them.